RT-PCR detection of exotoxin genes expression in multidrug resistant Pseudomonas aeruginosa - Tartor, Y H; El-naenaeey, E Y (Cellular and Molecular Biology, 2016)
Pseudomonas aeruginosa (PA) is an opportunistic pathogen responsible for causing a wide variety of acute and chronic infections with significant levels of morbidity and mortality. These infections are very hard to eradicate because of the expression of numerous virulence factors and the intrinsic resistance against antibiotics. Herein, this study analyzed antimicrobial susceptibility of PA isolated from broiler chickens and cattle as well as expression of five significant exotoxin genes (exoU, exoS, toxA, lasB, and phzM) and ecfX as internal control. Genomic DNA was amplified employing oprL gene for species specific detection of PA. The highest resistance was found to ampicillin, erythromycin, followed by, chloramphenicol, trimethoprim/ sulfamethoxazole and tetracycline, intermediately sensitive to ceftazidime, cefoperazone, and highly sensitive to gentamicin, levofloxacin, imipenem, ciprofloxacin and colistin. It appears that exoU+ and increased resistance to SXT may be co-selected traits. Vast majority of PA isolates expressed exoS (78.6%), exoU (71.4%) and both in more virulent strains. The ubiquity of toxA, lasB, exoU and exoS among PA clinical isolates is consistent with an important role for these virulence factors in chicken respiratory diseases and cattle mastitis that can be highlighted as potential therapeutic targets for treatment of infections caused by heterogeneous and resistant PA strains.